Jenis-jenis nyamuk di daerah kawasan industri sidangoli, halmahera dan maluku utara - Mardjan Soekirno (Perhimpunan Entomologi Indonesia, 2005)
Mosquitoes Species in Industrial Area Sidangoli, Halmahera, and North Maluku. A Study about mosquitoes species in industrial area Sidangoli, Halmahera, North Maluku was carried out from June 1993 to march 1994, Collections of mosquito from various habitats were done by six methods : (1) Collections of larvae and pupae from various habitats and reared in laboratory, (2) Night man-biting collection, (3) Night animal-biting collections or resting collections around cattle shelter, (4) Morning indoor resting collections, (5) Light trap collections, (6) Space spraying collections. All mosquitoes collected were than brought and identification to each species in the laboratory. The result showed that in industrial area Sidangoli have been identified 18 species of mosquitoes, which consist of 2 species Aedes, 6 species Anopheles, 8 species Culex, and 2 species Mansonia.